Dinasti Umayyah (661 - 750 M) : Peninggalan Sejarah dan Pengaruhnya dalam Perkembangan Islam - Lina Wati; Rika Wulandari; Septia Shylviana; Rapida Idami; Sirojul Fuadi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Umayyad Dynasty (661–750 AD) was the first Islamic dynasty to implement a hereditary monarchy and played a significant role in the massive expansion of Islamic rule. After the end of the Caliphate, power passed to Muawiyah ibn Abu Sufyan, who founded the dynasty and moved the center of government to Damascus. This study aims to examine the political, social, economic, and religious dynamics during the Umayyad Dynasty through qualitative methods and a literature review approach. The results of the study indicate that the success of the Umayyad expansion to Spain in the west and India in the east was driven by solid military strength, intelligent diplomatic strategies, and an established government administration system. In the economic aspect, the Umayyad Dynasty developed a taxation and currency system that supported the country's financial stability. Infrastructure such as roads, postal services, and communication systems were also improved to support connectivity between regions. In the social and cultural fields, interactions between various ethnicities and religions encouraged the development of science, art, literature, and architecture, including the emergence of a distinctive Islamic architectural style. However, the unequal social system between Arabs and non-Arabs (mawali), as well as discrimination within the government, fueled public dissatisfaction. Furthermore, sectarian conflict between Sunnis and Shiites exacerbated the domestic political situation. Inequities in the distribution of power, nepotism, and authoritarianism were the main causes of the weakening of support for the Umayyad government. Ultimately, this dynasty collapsed after being overthrown by the Abbasid Dynasty in 750 CE. This study emphasizes that the success of a government is greatly influenced by just leadership, an inclusive government system, and the ability to respond adaptively to socio-political challenges.